Proliferation and Osteogenic Differentiation of hMSCs on Biomineralized Collagen - de Melo Pereira, Daniel; Eischen-Loges, Maria; Birgani, Zeinab Tahmasebi; Habibovic, Pamela (Frontiers in Bioengineering and Biotechnology, 2020)
Biomineralized collagen with intrafibrillar calcium phosphate mineral provides an excellent mimic of the composition and structure of the extracellular matrix of bone, from nano- to micro scale. Scaffolds prepared from this material have the potential to become the next-generation of synthetic bone graft substitutes, as their unique properties make them closer to the native tissue than synthetic alternatives currently available to clinicians. To understand the interaction between biomineralized collagen and cells that are relevant in the context of a bone regeneration, we studied the growth and osteogenic differentiation of bone marrow derived human mesenchymal stromal cells (hMSCs) cultured on biomineralized collagen membranes, and compared it to the cell behavior on collagen membranes without mineral. Cells proliferated normally on both biomimetic membranes, and were more triggered to differentiate towards the osteogenic lineage by the biomineralized collagen. This was shown by the elevated mRNA levels of RUNX2, SPP1, ENPP1 and OCN after 3 days of culture, and COL1A1 after 14 days of culture on mineralized collagen. The mRNA levels of the tested markers of osteogenesis were lower on collagen membranes without mineral, with the exception of OCN, which was more highly expressed on collagen than on biomineralized collagen membranes. Expression by hMSCs of OPG, a gene involved in inhibition of osteoclastogenesis, was higher on biomineralized collagen at day 3, while M-CSF, involved in osteoblast-osteoclast communication, was upregulated on both membranes at day 3 and 14 of culture. Alkaline phosphatase activity of hMSCs was high on both biomimetic membranes when compared with cells cultured on tissue culture plastic. Cell-induced mineralization was observed on collagen membranes, while the high mineral content of the biomineralized membranes prohibited a reliable analysis of cell-induced mineralization on these membranes. In conclusion, we have identified that both collagen and biomineralized collagen support proliferation, osteogenic differentiation and mineralization of hMSCs, with biomineralized membranes having a more pronounced positive effect. These findings support the existing evidence that biomineralized collagen is a promising material in the field of bone regeneration.